A moderate dose of alcohol selectively reduces empathic accuracy - Thiel, Freya; Ostafin, Brian D.; Uppendahl, Jana R.; Wichmann, Lenka J.; Schlosser, Marco; Aan Het Rot, Marije (Psychopharmacology, 2018)
Rationale: Drinking alcohol is associated with various interpersonal effects, including effects on cognitive empathy. Empathic accuracy (EA) is a form of cognitive empathy concerned with perceivers’ accuracy in inferring a target’s thoughts and feelings. The effects of alcohol on EA have not previously been studied. Objectives: We examined the effect of a moderate alcohol dose on EA in social drinkers. Methods: Fifty-four men with varying levels of hazardous drinking according to the Alcohol Use Disorders Identification Test (AUDIT) participated in a randomized, double-blind, between-group study. The alcohol group received 0.56 g/kg alcohol in a vodka and tonic-mixed drink. The placebo group received tonic, with 4 ml of vodka sprayed on top. All participants performed an EA task that involved watching 16 videos of people narrating positive and negative emotional autobiographical events and continuously rating how targets felt while narrating. Results: There were no significant main effects of beverage condition on the EA task. There was an effect of the condition by AUDIT interaction for EA on the positive videos. Post-hoc simple contrasts revealed that in participants with lower AUDIT scores, the alcohol condition had lower EA for positive videos than the placebo condition. No significant main effect for condition occurred in the participants with higher AUDIT scores. Conclusions: The effect of condition in participants with lower AUDIT scores indicates alcohol selectively reduced EA in individuals low on hazardous drinking. This suggests either alcohol-induced impairments of EA for positive events or a positivity bias in men at low risk for alcohol dependency.
Created from Fastlane, Scopus look-up
Keywords: Alcohol consumption; Empathic accuracy; Risk for alcoholism; Social cognition

Developing a digital assistive tool for dementia patients and their caregivers: A qualitative study on needs, potential functions, practical requirements, user acceptance, and ethical considerations - Wichmann, Lenka; Reiff, Nele; Zintl, Sophie; Berking, Matthias (AAIC 2021: Technology and Dementia Preconference, 2021)

Multimodal, Valence-enhanced Approach-Avoidance Modification Training in Social Phobia and other Mental Disorders: Study protocol of Seven Randomized Controlled Trials - Streit, Hannah; Beitner, Lena; Rupp, Lydia; Keinert, Marie; Meixner, Marie; Wichmann, Lenka; Hager, Malin; Eskofier, Björn; Schuller, Björn W.; Berking, Matthias (2. Deutscher Psychotherapie Kongress, 2023)

Social identification and depression: A meta-analysis - Postmes, Tom; Wichmann, Lenka J.; Van Valkengoed, Anne M.; Van Der Hoef, Hanneke (European Journal of Social Psychology, 2019)
A meta-analysis of 76 studies (N = 31,016) examined the relationship between social identification and depression. Overall, individuals who identify highly with a group tend to report less depression (average rz = −.15). However, a large amount of variability between studies was observed. The 95% prediction interval, which indicates the true effect size that can be expected in future research, ranged from rz = −.50 to.19. The relationship between depression and social identification is more complex than previously assumed. Some variability is related to the social identification measure used. Studies that focused on identification with interactive groups (rz = −.28) had larger effect sizes than studies that focused on social categories (rz = −.11). Moreover, studies of non-stigmatized groups (rz = −.24) had larger effect sizes than studies of stigmatized groups (rz = −.10). In conclusion, the structure and social identity content of groups appear to play an important role in the relationship between depression and social identification.
Created from Fastlane, Scopus look-up
Keywords: depression; meta-analysis; social identification; social identity theory